Investigation of radial distributions of spectral line radiation emissivities in torsatron "Uragan - 3M" - Bondarenko, V.N.; Konovalov, V.G.; Tsybenko, S.A.; Voitsenya, V.S.; Volkov, E.D. (Вопросы атомной науки и техники, 2003)
The determination of the radial distributions of the radiation emissivity of the spectral lines relating to the working gas and impurities in the different ionization stages is an important object of the plasma spectroscopy diagnostics. The measured radiance chord distributions of the plasma in the specified spectral lines serve as a basis to obtain the radial distributions of the atom and ion concentrations. For the axially asymmetric magnetic surfaces in the torsatron "Uragan-3М" (U-3M) the approach of Pearce is realized by the computer program in an interpretation of the data on the radiance measured along the slanting lines of sight. The volumetric constants were computed with an interval between the lines of sight equals to 1 mm along the vertical plasma diameter in the DD cross-section. Such a small step excludes the roughness of the constants interpolation when turning to the radial distributions. The set of the 19 nested magnetic surfaces was chosen as an optimal one compared to any other number in the range of 10-24 surfaces. The chord measurements of the plasma volume radiance were carried out in the regular working regimes of U-3M. Using the experimental chord distribution data, the radial distributions of the radiation emissivity of several spectral lines were obtained: Hα, CV, CIII, OV, OIV, OIII, OII, etc. In the paper the radial profiles of concentrations of C⁴⁺ and C²⁺ carbon ions and hydrogen atoms in the ground and in excited states were presented found from the radiation emissivity data.